2020
DOI: 10.1038/s41598-020-70736-1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aorta diameter as a novel marker of diabetes incidence risk in elderly women

Abstract: the prevalence of diabetes mellitus is increasing worldwide, including the nation of poland. the aim of this prospective and observational study was to determine risk factors and the predictors of diabetes incidence in elderly women, and to calculate the diabetes incidence ratio in this population. Two-hundred women, aged 65-74, who were non-diabetic at baseline in 2012 were followed for 6.5 years. All women were checked for incident diabetes. In non-diabetic subjects, diagnostic procedures for diabetes were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, the level of acetone in the breath of diabetic patients ranges between 1.25 and 2.5 ppm, which exceeds those of healthy persons (0.2 and1.8 ppm) [11] . According to 2019 data of the World Health Organization (WHO), 463 million people worldwide are diabetic, and 1.6 million yearly deaths are related to diabetes [12] . Similarly, the WHO reported that lung cancer has over 2.09 million cases and 1.76 million deaths making it the most common, severe, and deadly cancer [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the level of acetone in the breath of diabetic patients ranges between 1.25 and 2.5 ppm, which exceeds those of healthy persons (0.2 and1.8 ppm) [11] . According to 2019 data of the World Health Organization (WHO), 463 million people worldwide are diabetic, and 1.6 million yearly deaths are related to diabetes [12] . Similarly, the WHO reported that lung cancer has over 2.09 million cases and 1.76 million deaths making it the most common, severe, and deadly cancer [13,14] .…”
Section: Introductionmentioning
confidence: 99%